China Looks at the West : Identity, Global Ambitions, and the Future of Sino-American Relations - Ford, Christopher A., 1967- (Book collections on Project MUSE., 2015)
Chinese leaders have long been fascinated by the US, but have often chosen to demonise America for perceived cultural and military imperialism. Especially under Communist rule, Chinese leaders have crafted and re-crafted portrayals of the US according to the needs of their own agenda and the regime's self-image. Christopher A. Ford investigates what these depictions reveal about internal Chinese politics and Beijing's ambitions in the world today.